A comparison of protocols for measuring forces during landing on competition mats in gymnastics - Buxton, E. L.; Hiley, M. J.; Yeadon, M. R. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
During apparatus dismounts gymnasts land from up to 4 m above the landing surface. The gymnast needs to withstand high impact forces and the use of landing mats allows gymnasts to attenuate the forces with their landing strategy and interaction with the landing mats. Competition landings from various gymnastics apparatus involve the use of a 200 mm thick landing mat, with an additional 100 mm thick mat placed on top. The purpose of this research was to investigate the experimental protocols for measuring forces using force platforms during landings on competition mats. Three experimental protocols were compared, each of which used a force platform underneath landing mats in various set-ups. In Protocol 1 the mats were placed directly onto the force platform; in Protocol 2 the mats were placed on an enlarged raised extension; in Protocol 3 smaller mats were used with the extension. Differences between the vertical landing velocities calculated from kinematic data and from force platform data were used to assess how much impulse was transferred to the force platform in each of the protocols. Protocol 3 was the preferred method for collecting landing forces and resulted in a mean percentage velocity absolute difference of less than 2% for both one-mat and two-mat conditions. This study demonstrates the importance of keeping the landing mats clear of the force platform surroundings during the whole of the landing phase.